Electrochemical behavior of fungicide tebuconazole and its voltammetric determination on an oxygen-terminated boron-doped diamond electrode - Šelešovská, Renáta; Sokolova, Romana; Krejčová, Kateřina; Schwarzova-Peckova, Karolina; Mikysek, Tomáš; Matvieiev, Oleksandr (Elsevier Science SA, 2023)
The first study on electrochemical oxidation of triazole fungicide tebuconazole was performed using an oxygen-terminated boron-doped diamond electrode. The irreversible anodic process occurring at + 1.75 V (vs Ag/AgCl/KCl(sat.)) in 0.1 mol/L HNO3 was studied by cyclic voltammetry, IR spectroelectrochemistry, and density functional theory calculations. The oxidation of tebuconazole leads to the formation of the hydroxylated and dihydroxylated derivatives on the 4-chlorophenyl moiety. Also, the corresponding o-quinone derivative was detected. Further, the anodic signal was used to develop a differential pulse voltammetric method for tebuconazole determination with the following parameters: linear dynamic range from 5.0 x 10-7 to 8.3 x 10-5 mol/L and limit of detection of 1.5 x 10-7 mol/L. The method was successfully applied to the analysis of a commercially available pesticide formulation and model samples of river water after preconcentration of tebuconazole using Amberlite (R) IRC120 H ion-exchange resin in H+ cycle.
Elektrochemické chování fungicidu tebuconazolu a jeho voltametrické stanovení na kyslíkem terminované borem dopované diamantové elektrodě
Keywords: Tebuconazole; Triazole fungicide; Voltammetry; Boron -doped diamond electrode; Oxidation; IR spectroelectrochemistry; Tebuconazol; Triazolový fungicid; Voltametrie; Borem dopovaná diamantová elektroda; Oxidace; IR spektroelektrochemie